Becoming Frum : How Newcomers Learn the Language and Culture of Orthodox Judaism - Benor, Sarah, 1975- (Book collections on Project MUSE., 2012)
When non-Orthodox Jews become frum (religious), they encounter much more than dietary laws and Sabbath prohibitions. They find themselves in the midst of a whole new culture, involving matchmakers, homemade gefilte fish, and Yiddish-influenced grammar. Becoming Frum explains how these newcomers learn Orthodox language and culture through their interactions with community veterans and other newcomers.